(untitled) (Altre Modernità, 2015)
Into the poetic of descent proposed by the literary critic Cárcamo-Huechante, Blanca Varela developes a poetry in relation with corporality and deterioration. Existencialism thought connects with the search of a material poetic word, fill with corporal, byologic elements. Hunger is the privileged metaphor in the process of materialization of poetic writing. It is social and linguistic demand against unjustice and the impoverished language system, also into literary tradition. We propose an exegesis of metaphoric configuration of hunger through a thematic and a stylistic line of research, which embodies sense and sound of poetic word.